AN EXAMINATION OF ELECTRONIC BANK SERVICE QUALITY AND ITS SIGNIFICANCE ON ELECTRONIC SATISFACTION AND ELECTRONIC LOYALTY - Islam Mohammad Siamul; Awais Dastgeer; Sultana Zakia; Shakir Iqbal; Qaria Aqeela Bibi (Policy Research Journal, 2025)
This study aims to examine the quality of electronic banking (e-banking) services and their impact on electronic satisfaction (e-satisfaction) and electronic loyalty (e-loyalty). A comprehensive review of the literature on service quality, e-banking, and customer satisfaction was conducted to develop a conceptual framework for the study. The study used a survey method to collect data from 400 e-banking customers, and structural equation modeling was employed to analyze the data. The findings of the study reveal that e-service quality positively influences e-satisfaction and e-loyalty. Moreover, e- satisfaction mediates the relationship between e-service quality and e-loyalty. The study contributes to the existing literature by highlighting the importance of e-service quality in enhancing customer satisfaction and loyalty in the e-banking sector. The findings of the study have significant implications for e-banking managers and policymakers, as they can use the results to improve the quality of e-banking services and enhance customer satisfaction and loyalty.